2020
DOI: 10.22460/project.v3i3.p414-419
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Students’ Vocabulary Through Total Physical Response

Abstract: Learning English during this time globalization is exceptionally critical. People aspire to speak fluent in English. This proves that the presence of English during this time globalization is exceptionally imperative and considering that English is an international language. However, many Indonesians people cannot master vocabularies well, due to lack of understanding when studying in the class. The population of students were 130 within the eighth grade, but researcher using 1 class, there are 35 stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In addition, the TPR teaching method can arouse students' interest in learning English. The TPR method is an effective method to improve students' vocabulary mastery (Khakim & Anwar, 2020;Gayanti & Satriani, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the TPR teaching method can arouse students' interest in learning English. The TPR method is an effective method to improve students' vocabulary mastery (Khakim & Anwar, 2020;Gayanti & Satriani, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore TPR teaching method can make students more attractive learning in the class so that they learn English through body movements without too much explicit pressure. (Gayanti & Satriani, 2020) found the vocabulary improvement of Total Physical Response (TPR) in the eighth grade. The finding of the qualitative method was showed the result that students can improve their vocabularies well through TPR.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…A glaring example of this method is the singing of the learners, not only for fun, but also for incorporating movements that they can always remember to bring back to their own minds the vocabulary, they have previously learned. Gayanti and Satriani (2020) concluded that this method could be effectively used to help EFL learners acquire new vocabulary as it stimulates them to be more active in learning, memorizing, and saying new words with more confidence. It has been reported by the Lincoln Center of Albania ( 2014) that this method helps EFL learners recognize and memorize new words due to its memorable activities that EFL learners cannot forget easily.…”
Section: The Total-physical Response and Teaching Vocabularymentioning
confidence: 99%
“…This positive learning outcome occurred since the learners experienced more enjoyable vocabulary learning activities prompting them to memorize as many new words as possible. The ultimate interesting study was done by Gayanti and Satriani (2020). They discovered that total physical response promoted more proactive engagement for EFL learners engaging in vocabulary class since a higher degree of anxiety was completely banished when uttering some new words.…”
Section: Introductionmentioning
confidence: 99%